Voltammetric and amperometric detection on nitrated explosives (a review) - Barek, Jiří; Fischer, Jan; Wang, Joseph (Univerzita Pardubice, 2011)
In this article, possibilities of electrochemical detection of various explosives containing electrochemically active nitro group are reviewed. Attention is paid both to the use of traditional mercury electrodes and non-traditional, recently developed electrodes based on mercury amalgams, bismuth films, boron-doped diamond films and carbon films in voltammetric and amperometric mode. Screen-printed, chemically modified and/or biologically modified electrodes are discussed as well. Advantages and disadvantages of electroanalytical techniques are briefly discussed together with their possible combination with a preliminary separation and preconcentration using liquid-liquid extraction or solid phase extraction. Electrochemical detection of reducible explosives in flowing media using above mentioned electrodes is briefly disused, attention being paid to wall-jet, thin-layer, tubular and cylindrical arrangement of the detection system.
Keywords: explosives; mercury electrodes; amalgam electrodes; bismuth film electrodes; boron-doped diamond film electrodes; carbon film electrodes; voltammetry; amperometry